Main groups by risk behavior on HIV infection according to the analysis of youths’ preventive awareness. - Detsyk, O. Z.; Basarabа, T. P. (Medicni Perspektivi, 2016)
To study the awareness of young people on HIV prevention and highlight the main groups of risk-behaviorin the city Ivano-Frankivsk there was conducted anonymous survey of 1926 respondents aged 14 to 24 years in schools and educational institutions of different levels of accreditation, children’s orphanges and at the Regional Centre of AIDS Prevention and Control. It was found that 70% of people aged 14-24 years do not have sufficient knowledge about HIV prevention. Preventive awareness improves with age, and persons of the senior school age and adolescence (OR=1.77; 95% CI=1.37-2.29) female (1.33; 1.10-1.61) are the risk-groups of HIV infection by age and sex.. There was proved that risk-behavior groups are also teenagers with deviant social behavior (3.14; 1.59-6.19), as well as non-medical college students (1.81; 1.47-2.23), the natives of rural areas (1.38; 1.11-1.71). The data should be considered in the development of scientifically based measures of primary prevention of HIV among the identified target risk groups.